PERAN ORGANISASI BALA KOMANDO PEMUDA MELAYU DALAM MEMPERKUAT SIKAP TOLERANSI UMAT BERAGAMA DAN ETNIS DI KOTA SINGKAWANG - ananda, erlian rizki (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This study aims to determine the program, role of the program, inhibiting factors of the Singkawang City Malay Youth Command in strengthening religious and ethnic tolerance in Singkawang City, as well as a description of the attitude of religious and ethnic tolerance in Singkawang City in the Singkawang City community. The research method used is descriptive with a qualitative approach. The data sources for this study were members and young commanders of the Singkawang City Malay Youth Command, as well as the community in Singkawang City. Data were obtained through observation, interviews, and secondary data. The results of this study indicate that the Singkawang City Malay Youth Command program in strengthening tolerance is Friday blessings, people give alms, donate blood and circumcision, participate in securing the Cap Go Meh, participate in dango riding activities, social activities and youth development, and torch parades. The role of the Singkawang City Malay Youth Command program has been running quite well in strengthening religious and ethnic tolerance in Singkawang City, this can be seen from the role of the work program that has been implemented. There is a Malay Youth Commando program that is implemented annually, monthly and implemented according to the situation and conditions of members and conditions in Singkawang City. Inhibiting factors of the Malay Youth Commando of Singkawang City in strengthening religious and ethnic tolerance in Singkawang City, for example, time issues, because most members of the Malay Youth Commando of Singkawang City are active workers, every time they carry out activities or programs they always encounter obstacles, in terms of funding or finances so that funds are obtained from members' own funds and donor assistance and there is no secretariat. The description of the attitude of tolerance of religious and ethnic communities in Singkawang City can be seen from the community being able to accept differences and continue to live side by side, for example, there are 3 different cultural activities, for example, cap gomeh, a cultural activity of the Chinese ethnic group, naik dango, an activity of the Dayak ethnic group, and the torch parade, an activity of the Malay ethnic group, as evidenced by the smooth running of the activities and the absence of problems regarding cultural activities that are different from each ethnic group in Singkawang City.